Effect of Applied Information-Motivation-Behavioral Skills Program for Weight Control on Gestational Weight Gain of Overweight and Obese Pregnant Women - khante, Oraya; Xuto, Piyanut; Piyaporn (Journal of The Royal Thai Army Nurses, 2026)
This randomized controlled trial aimed to the applied information- motivation-behavioral skills program for weight control of overweight and obese pregnant women. The sample consisted of 44 overweight and obese pregnant women, divided into an experimental group (22 cases) and control group (22 cases). Data were collected using a questionnaire on personal data and obstetric history, a weight control behavior questionnaire (with the reliability of the questionnaires being 0.91 respectively), and a pregnant women’s weight record form. Data were analyzed using descriptive statistics, Fisher’s exact test, two-group paired t-test, and two-group independent t-test.The results showed that the mean excessive weight gain in the experimental group after participation in the program increased significantly less than before the program (p < .05) and the mean excessive weight gain in the experimental group was significantly lower than that in the control group receiving standard care (p < .05).